(untitled) (Interdisciplinary Studies Journal, 2024)
This article presents an investigation into the Basic Education school, understanding it as a privileged space for social relationships, in which social markers are highlighted, and, according to practices and eventual relationships, one can contribute to overcoming prejudices or lead to the reproduction of oppression. In this way, the school functions as a disciplinary device of normalization, seeking to homogenize subjects, with those who are far from expected being subordinated. The objective of the investigation was to contribute to the training of teachers and their practices, based on the understanding of intersectionality and reflections on the oppression and subalternization that can occur in the school environment. Intersectionality was taken as an approach to enable reflection on teaching practice and overcoming oppression and subordination in the school space, discussing teacher training from this perspective. As a methodology, we started from the records in the field diary, from the memories of a vivid scene by one of the authors, which took place in a Basic Education school of the Municipal Public Network in a city in the Metropolitan Region of Porto Alegre, analyzing it from time to time. from the theoretical-methodological perspective of intersectionality. It was concluded that this perspective can contribute to the training of teachers and qualification of their practices, through reflections on situations of oppression experienced at school and the search for overcoming them, leading to a school that contributes to social relations, respecting them. the diversity of subjects.